Non-Destructive Testing of Quay Walls Using Submersible Remotely Operated Vehicles (ROV) In Waterways Around the North Sea Coast - Venkatesh, Vishnu; Kodoth, Krishnaraj; Jacob, Ashish Anthony; Upadhyay, Vineet; Jhunjhunwala, Tanuj; Rajagopal, Prabhu; Ali, Mohammad Nazeer; Balasubramaniam, Krishnan (OCEANS 2022 - Chennai, 2022)
The North Sea, with a coast length of 1590 km, is amongst the most active commercial shipping route in the world, and is subject to harsh environmental conditions throughout the year. Coastal protecting measures defend waterways around the North Sea coast against storms, rising sea levels, and corrosion. Quay walls, one of the most widely used coastal protection system, have been one of the fundamental building blocks of the economic system. They are designed to enable ship moorings and absorb impacts from vessels. Further, quay walls are used to allow shipment of goods to the vessels using heavy equipment. They must withstand varying water levels, environmental conditions, loads being carried in and out of the ports. Periodic asset maintenance of quay walls is therefore crucial to ensure uninterrupted services and minimum downtimes, and to prevent catastrophic damages and loss of lives.Quay walls are subject to numerous structural damages including interlock damage, scouring, impact damage, and corrosion of concrete, reinforcement, and steel components. Continuous inspection programs are required to timely maintain, and repair associated infrastructure. Conventionally, the underwater sections of the quay wall are inspected by professional divers carrying underwater cameras and sensors to perform visual and ultrasonic thickness measurement. However, diver-based methodologies are often restricted by limited operational durations, depths, and safety risks. Further, the waterways connected to the North Sea are subjected to numerous challenges including as dense marine growth, dynamic variations in water visibility, underwater currents or flow, and operation in confined spaces. To overcome these challenges and inherent risks associated with manned underwater operations, an alternative inspection approach using remotely operated robotic vehicles (ROV) indigenously developed by Planys BV is proposed in this paper. ROVs have several key advantages in comparison to the conventional-manned operations including unlimited endurance, and depth of operation, live video streaming, improved data quality, and defect geotagging to improve result repeatability.These ROVs are controlled remotely from a safe location by a pilot. They are also compact and lightweight, deployable by a crew of two personnel. They carry underwater cameras and lights for live visual inspection, sonic and ultrasonic transducers for sonar surveys and ultrasonic thickness measurement, respectively. This paper presents a case study of inspecting sheet pile infrastructure using ROVs in waterways connecting the North Sea in Western Europe. Key details explaining the components of the ROV, and methodology of operation are discussed. Exemplary results from visual inspection and ultrasonic thickness measurement are depicted, showing satisfactory quality of data collected. Furthermore, details of data analysis and representation implementing state-of-the-art digital analysis dashboard to enable rapid and accurate interpretation, are presented.Key limitations of using freely swimming ROVs are described from the viewpoint of operational efficiencies and rate of inspection. Recommendations on development of next generation of robotic crawler devices for enhanced commercially viable inspection routines are discussed. The work presented in the paper may be of interest to authorities, asset owners and managers of marine assets, operating both, inland and nearshore.